DIVERSIFIKASI PEKERJAAN NELAYAN DI KECAMATAN SUNGAI RAYA DAN KECAMATAN SUNGAI RAYA KEPULAUAN KABUPATEN BENGKAYANG - Agustinus, Edy (JURNAL BORNEO AKCAYA, 2015)
The second-rate welfare of coastal society complicated for them to fill their needs. In order to improve their welfare, frequently fishermen to diversify jobs. The aim is to determine the diversification of fishermen work in an effort to improve their welfare in subdistrict Sungai Raya and Sungai Raya Kepulauan Bengkayang. Research conducted by 2014 it is qualitative descriptive. The results showed that the sector which has been the economic foundation of society in the coastal districts located in three sectors, namely agriculture, industry and trade. While intensifying the range of her work focused on the agricultural sector sub sector of fisheries. Meanwhile, job diversification of fishermen in the research sites are: first, diversification of work fishermen skipper or boat owner is managing mine services, facilities or home stay accommodation services and cultivate crops of nutmeg and clove. Second, diversification of the individual fishermen do business drying fish with methods of curing or smoked, rent a motor boat to tourists, cultivate seaweed, making belacan, and opened a rental home stay for tourists. And third, a diversified family of fishermen that workers be porters of goods, charter-boat captain skipper-owned fishing boats or individuals, freelance workers in oil palm plantations, and into wage laborers to pick shrimp catches of fishermen.